Construction management students' perceptions of ethics in tendering - Zarkada, Anna K.; Skitmore, R. M.; Runeson, G. (My University, 1998)
The current approach to the problem of collusive tendering in construction is to devise systems for detecting collusive tendering after the contract is awarded and more often than not even after the project is completed. ie after the high moral and pecuniary costs of collusion have already been incurred by society. Moreover, punishment through legal action not only fails to recover the costs but it also burdens society with the judiciary costs. An alternative approach is to design systems that prevent collusion from happening in the first place. For this, we need a deep understanding of the mechanisms of the practice as well as an insight into the decision making process of the person that instigates or negotiates, accepts and carries out an agreement to break the law and disregard codes of ethics. This paper presents the initial findings of an investigation into the behavioural, aspects of collusive tendering in the construction market in Australia. It is exploratory and empirical and depicts behavioural intent and attitudes of part time, final year construction management students and attempts to link them to their university training through an examination of the ethics component of their curriculum. First, a brief literature review introduces the theoretical model of moral decision making in tendering. Then the research method is explained and the students’ responses are summarised. The paper concludes with a discussion of the implications of the study.
Keywords: Professional; development; Ethics; Tendering; Collusion